Ethics of Learning in Philosophy Perspective - Siti Nur Afifah; Kun Nurachadijat; Siti Ulfah Fauziah (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2022)
Ethics in learning is an important thing that must exist. Where when we are studying a science then automatically we must be able to master it and understand the science. But it's not enough to just understand because one of the concepts of learning is to make a science a lesson so that we become better than before. The method that the author uses is the literature review method where the goal is to explore existing theories and encode them with other theories from other sources. The aim is to provide additional information to readers and to become material for review in the development of other sciences.